Synthesis and Evaluation of ABO3 Perovskites (A=La and B=Mn, Co) with Stoichiometric and Over-stoichiometric Ratios of B/A for Catalytic Oxidation of Trichloroethylene - Razieh Alagheband; Sarah Maghsoodi; Amirhossein Shahbazi Kootenaei; Hassan Kianmanesh (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
In this contribution, perovskite catalysts (ABO3) were probed that site A and site B were occupied by lanthanum and transition metals of manganese or cobalt, respectively, with stoichiometric ratios as well as 20 % over-stoichiometric ratios of B/A. The perovskite samples were synthesized using a gel-combustion method and characterized by BET, XRD, SEM and O2-TPD analyses. After mounting in a fixed bed reactor, the catalysts were examined in atmospheric pressure conditions at different temperatures for oxidation of 1000 ppm trichloroethylene in the air. Evaluation of over-stoichiometric catalysts activity showed that the increased ratio of B/A in the catalysts compared to the stoichiometric one led to BET surface area, oxygen mobility, and consequently catalytic performance improvement. The lanthanum manganite perovskite with 20 % excess manganese yielded the best catalytic performance among the probed perovskites.